Positive rolandic sharp waves in the EEG of the premature newborn: a five year prospective study. Issue 7 (July 1992) - Marret, S; Parain, D; Jeannot, E; Eurin, D; Fessard, C
Abstract : In a prospective study of 301 premature newborn infants, neonatal tracings were done to evaluate the use of the electroencephalogram (EEG) and positive rolandic sharp waves (PRSW) in the diagnosis and prognosis of periventricular leucomalacia. Each infant had ultrasonographic studies and standardised neurological examinations at 1 year of age or later. Two hundred and eighty infants were followed up at 1 year. This study demonstrated that the absence of PRSW was correlated with a favourable motor development (98.2%) and confirmed the great value of PRSW in the diagnosis and the prognosis of periventricular leucomalacia. PRSW were sensitive (98%) and specific (84%) markers of developmental motor disability and were a sensitive (96%) marker of severe spastic diplegia. A frequency above 2/minute was a specific (92%) sign of severe spastic diplegia. Social and language developmental abnormalities were not correlated with the neonatal EEG.